Matthew - Brown, Jeannine K.; (1961-...) (U.S.A, 2018)
In this latest addition to the Two Horizons New Testament Commentary series, biblical scholar Jeannine Brown and theologian Kyle Roberts together illuminate the Gospel of Matthew for pastors, scholars, and serious students of Scripture. Including an original translation of the text along with section-by-section commentary, this volume features chapters on (3z(Bthinking theologically with Matthew(3y (Babout such themes as kingdom, Christology, the Holy Spirit, and discipleship. Brown and Roberts also offer constructive theological engagement with a number of contemporary viewpoints, including feminist, global, political, and ethical (post-Holocaust) perspectives. At once interdisciplinary and insightful, their commentary will appeal to a wide readership.s
Keywords: Bible -- Matthew